PERBEDAAN KEMANDIRIAN REMAJA SMA ANTARA YANG SINGLE FATHER DENGAN SINGLE MOTHER AKIBAT PERCERAIAN (Jurnal Psikologi Udayana, 2015)
Structure of the family is one of the factors that builds the independence of adolescents. Nowadays, it is uncommon to find families that are not united due to divorcement. The condition where families are no longer united (single parent) will affect the independence of adolescents. Independence of adolescence is the ability to organize behavior and decision without being dependent on parents (Steinberg, 2002). The purpose of this research is to see the difference of independence between senior high school adolescents with single mother and adolescents with single father due to divorcement. A total of 64 senior high school adolescents in Bali in aged 15-18 years who have single parents due to divorcement were included as subjects in this quantitative research, with comparison approach. The sampling technique that was used in this research was cluster sampling. Measuring instrument used in this research was Independence Scale (34 item, rxx=0.889). The statistical technique used to process the data of this study is a parametric test of independent t-test. Based on the outcome of this research, it appears that there is no significant difference between the independence of senior high school adolescents with a single father nor single mother due to divorcement (t=1.212) with p equal to 0,230 (p>0,05). Keyword: Autonomy of Adolescence, single father, single mother.